Risk assessment and risk-driven quality assurance : 4th International Workshop, RISK 2016, held in conjunction with ICTSS 2016, Graz, Austria, October 18, 2016, Revised selected papers /: 4th International Workshop, RISK 2016, held in conjunction with ICTSS 2016, Graz, Austria, October 18, 2016, Revised selected papers. (2017) - Unknown
No abstract available